VIDEO AND ANIMATION TOOLS FOR REPRESENTATION OF INFORMATION - Tobylov, K.T.; Danilova, V.V.; Dаgalov, I. (PUBLISHINGS of Kostanay State Pedagogical University, 2017)
With the development of computer multimedia technologies in the field of education, the concept, features, potential of multimedia technology and multimedia visualization of information are revealed, allowing to present content. The aspects of the implementation of the principle of visibility in teaching at a qualita-tively new level are revealed. The review of on-line multimedia resources is given.
Keywords: multimedia systems; platform; telecommunication; representation of information; World Wide Web; medium; message; image